2013
DOI: 10.3765/exabs.v0i0.764
|View full text |Cite
|
Sign up to set email alerts
|

Calculating Frequency of Occurrence of ASL handshapes

Abstract: Here we discuss an investigation of handshape markedness based on frequency of occurrence in an ASL database. Using a database of the most frequently used signs in a corpus of child language and other early-acquired signs we examined the handshapes of approximately 1000 signs by using two annotation systems, BTS and Stokoe annotation. Results indicate that the distribution of handshape use on the dominant and non-dominant hands is consistent with the predictions set forth by previous researchers in their exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Estimates based on the Stokoe system (Stokoe et al, 1965) have found that handshapes that select all four fingers (B, A, C, and 5) are among the most frequent, followed by those that select the index finger (G, X, L); those that select other fingers are less common (Klima & Bellugi, 1979; Henner, Geer, & Lillo Martin, 2013). Focusing only on single selected fingers, Ann (1996) also found that for both ASL and Taiwanese Sign Language, the index finger was used more than the thumb, followed closely by the pinky finger.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates based on the Stokoe system (Stokoe et al, 1965) have found that handshapes that select all four fingers (B, A, C, and 5) are among the most frequent, followed by those that select the index finger (G, X, L); those that select other fingers are less common (Klima & Bellugi, 1979; Henner, Geer, & Lillo Martin, 2013). Focusing only on single selected fingers, Ann (1996) also found that for both ASL and Taiwanese Sign Language, the index finger was used more than the thumb, followed closely by the pinky finger.…”
Section: Resultsmentioning
confidence: 99%
“…All of these patterns are reflected in our data on selected fingers (Figure 3, top left panel). The most common handshapes in the Stokoe system use fully extended flexion positions, with other positions being less common (Klima & Bellugi, 1979; Henner, Geer, & Lillo Martin, 2013). This too is reflected in our flexion counts (Figure 3, bottom left panel) where signs with fully extended flexion account for 49% of the database.…”
Section: Resultsmentioning
confidence: 99%
“…While ASL phonology is widely studied, only a few studies have investigated phonotactic probabilities and the phonotactic constraints on the formation of ASL signs ( Ann, 1996 ; Henner, Geer, & Lillo-Martin, 2013 ). Phonotactic probability is the frequency with which a phonological feature or combinations of features occur in the lexicon.…”
Section: Major Properties Of Signs In Asl-lex 20mentioning
confidence: 99%
“…We also leave out F‐, which has only two fingers that are [+contact]—but behaves more like a surface‐drawing handshape (which typically has all five digits in the same position—extended or flexed, spread or not). This might seem a regrettable omission, since the use of F‐, while infrequent in the frozen lexicon (Henner, Geer, & Lillo‐Martin, 2013), is common in conversation as a classifier. However, we found only one (distinct) lexical sign that used it in drawing.…”
Section: Dictionary Study Of Aslmentioning
confidence: 99%